Investigating the Role of Self-Regulated Learning Strategies in Online Bachelor’s Degree Completion Rates in Ghana - Mohammed, Amina (International Journal of Online and Distance Learning, 2024)
Purpose: The aim of the study was to investigate the exploring the relationship between digital literacy skills and student success in online science courses in Indonesia. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Recent research on digital literacy skills and student success in online science courses in Indonesia indicates a strong link between proficient digital skills and academic achievement. Students who demonstrate competence in areas like information literacy and online collaboration tend to perform better and show higher levels of engagement in their courses. This highlights the significant impact of digital literacy on enhancing learning outcomes and fostering self-directed learning among Indonesian students in online science education. Unique Contribution to Theory, Practice and Policy: Social cognitive theory, control-value theory of achievement emotions & cognitive load theory may be used to anchor future studies on the exploring the relationship between digital literacy skills and student success in online science courses in Indonesia. Educational institutions should integrate explicit SRL instruction into online curriculum design. Policymakers should develop guidelines and standards that promote the integration of SRL strategies into online education policies.